2020
DOI: 10.1002/rra.3585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river ice break‐up on organic‐matter dynamics and feeding ecology of aquatic insects

Abstract: Disturbance shapes the structure and function of aquatic communities and ecosystems, but the dynamics of ice are a less studied dimension of the disturbance‐regime of rivers. We investigated effects of a river‐ice regime on organic‐matter dynamics and feeding ecology of aquatic insects. Samples of biofilm and aquatic insects for gut content analysis were collected monthly from Big Creek, a sixth ‐ order tributary of the Middle Fork Salmon River in central Idaho, USA, during winter 2010–2011. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…Filamentous green algae are likely the source of ALA, diatoms are likely the source of EPA, and terrestrial detritus is likely the source of LIN, the precursor to ARA of shredding invertebrates (Cummins et al, 1989). However, our findings contrast with previous studies of salmonfly diets which found a much greater dependence on autochthonous material, including diatoms and animal parts (Blackadar et al, 2020;Freilich, 1991;. Both seasonal and site-specific factors may contribute to the differences between our findings and previous studies.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Filamentous green algae are likely the source of ALA, diatoms are likely the source of EPA, and terrestrial detritus is likely the source of LIN, the precursor to ARA of shredding invertebrates (Cummins et al, 1989). However, our findings contrast with previous studies of salmonfly diets which found a much greater dependence on autochthonous material, including diatoms and animal parts (Blackadar et al, 2020;Freilich, 1991;. Both seasonal and site-specific factors may contribute to the differences between our findings and previous studies.…”
Section: Discussioncontrasting
confidence: 98%
“…Salmonflies are often classified as shredders and presumed to consume allochthonous detritus. However, the few studies that have quantified salmonfly diets by gut content analysis indicate substantial variation in allochthony by location and season, with sometimes heavy reliance on autochthonous production (Blackadar et al, 2020;. In addition to traditional methods of gut content analysis, fatty acid (polyunsaturated fatty acid [PUFA]) composition of macroinvertebrate tissues can provide information on origins and quality of macroinvertebrate diets (Lau et al, 2009;Torres-Ruiz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to consider how the hydrogeomorphic setting of river channels influences how ice develops on that template and influences underlying productivity patterns (e.g., relative balance of benthic vs. pelagic productivity). For instance, ice tends to form and break up later in larger, deeper channels as a result of their thermal inertia (Buffin-Bélanger et al, 2013;Turcotte et al, 2012) and lateral variation of ice duration across the channel is common, as ice tends to form earlier and break up later in shallow, higher residence time locations like off-channel areas, backwaters, or channel margins (Blackadar et al, 2020;Brown et al, 2011;Danks, 2007). Therefore, typically productive channel margins and backwaters will have limited light for longer periods during the winter, while along the thalweg or the main channel, the flow may be too turbulent for primary producer communities to establish (Uehlinger, 2006;Uehlinger & Naegeli, 1998; Figure 2).…”
Section: Ecosystem Energeticsmentioning
confidence: 99%
“…Though metabolism may be low during the winter months, either due to low temperature or light impediment from ice, annual productivity and metabolism often depend on the timing and length of the snow-covered season (Casson et al, 2012;Mulholland et al, 2009). In addition, winter ice breakup and freeze-up were shown to be a driving force in maintaining "good quality" algal biomass and subsequent insect diversity throughout the year (Blackadar et al, 2020). In contrast to the milder winters of deciduous headwater catchments, Arctic streams (above the Arctic Circle) experience long winters and are likely to completely freeze due to low sustained winter temperatures and reduced flow (Huryn et al, 2014;Shogren et al, 2020).…”
Section: Ecosystem Energeticsmentioning
confidence: 99%
“…Excess deposition of sediment in coarse substrates will cover and inundate the gravels, thereby eliminating the habitat where many invertebrates live [91][92][93][94]. Ice regimes in temperate rivers can also affect organic-matter dynamics and feeding ecology of aquatic insects [95].…”
Section: Ecological Considerationsmentioning
confidence: 99%